Students Perceptions, Satisfactions and Challenges on Problem-Based Learning (PBL): A Survey Study Among Final Year Pharmacy Students - Engku Nuraishah Huda E. Zainudin; Fakhira Damia Khaidir; May Khin Soe; Nurul Asyiqin Yusof; Khairool Azizul Mohammad (Journal of Pharmacy)
Introduction: Problem-based learning (PBL) is being adopted more frequently in pharmacy education to enhance skills such as problem-solving, and self-directed learning. However, thorough research on pharmacy students’ perceptions and satisfaction towards PBL in Malaysia remains inconclusive. This study aims to explore students’ views, satisfaction, and obstacles regarding PBL in pharmacy education especially to improve critical thinking, interpersonal skills, and problem-solving skills. Method: A cross-sectional study using a validated closed and open-ended questionnaire consisting of 22 statements was distributed among 84 final-year pharmacy students. Results: Eighty-four final-year pharmacy students participated in this study. Findings revealed that the majority agreed with statements on benefits that PBL significantly contributed to their knowledge acquisition (100.0%), stimulated the exploration of basic scientific concepts (98.8%), and enhanced their understanding in selecting both pharmacological and non-pharmacological approaches in disease management (97.6%, 95.2% respectively). The consensus extended to the belief that PBL fostered interactions with peers (91.7%), improved problem-solving skills (95.2%) and enhanced interpersonal skills (95.2%). Students expressed confidence in their instructors’ clarity (92.9%) and clear answers to questions (90.5%). Most felt comfortable participating in discussions (69%), and nearly all students were satisfied with their group members’ cooperation (95.2%). Although, most findings highlight positive aspects of PBL, this study also identified three major challenges in PBL implementation, namely 1) insufficient time for PBL preparation, 2) lack of teamwork, and 3) difficulty in finding adequate reading materials. Conclusion: Overall, these findings highlight positive aspects of the PBL experience among respondents. Future research should consider diverse student populations, conduct longitudinal studies, and explore instructors’ perspectives.